Determination of the Antimicrobial and Biochemical Content of Black Carrot (Daucus carota ssp. sativus var. atrorubens Alef.) - Gül, Gizem; Yaman, Cenker; Turu, Dilay; Benek, Atakan; Pala, Rüveyde; Sayım, Merve Ülkü; Bozyel, Mustafa Eray; Canlı, Kerem (Afyon Kocatepe Universitesi Fen Ve Muhendislik Bilimleri Dergisi, 2025)
This study aimed to assess the antimicrobial activity of Daucus carota ssp. sativus var. atrorubens Alef. plant through disk diffusion and MIC (Minimum Inhibitory Concentration) methods, evaluate its antioxidant activity via the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, and analyze its biochemical composition using GC-MS (Gas Chromatography-Mass Spectrometry). A total of 28 microorganisms were utilized, comprising 10 standard isolates, 1 clinical isolate, 7 food isolates, 9 multidrug-resistant strains, and 1 standard yeast. The most significant inhibition zones in the disk diffusion test were observed with measurements of 8-8-10 mm for the Staphylococcus aureus strain, 9-11-16 mm for the Enterococcus faecium strain, and 9-9-9 mm for the Streptococcus pneumonia strain. The MIC test revealed the highest inhibition at a concentration of 1.18 mg/ml against Enterococcus faecium strain. Antioxidant activity, determined using the DPPH method, exhibited the highest activity at a concentration of 1000 µg/mL. GC-MS analysis identified Linoelaidic acid (18.30%) as the predominant compound. Overall, the study detected antimicrobial activity against 21 out of the 28 tested microorganisms, highlighting the potent antimicrobial and antioxidant properties of D. carota ssp. sativus var. atrorubens, alongside its rich biochemical composition.